2023
DOI: 10.3390/cancers15205093
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer and Bone Mineral Density in a U.S. Cohort of Middle-Aged Women: Associations with Phosphate Toxicity

Ronald B. Brown,
Philip Bigelow,
Joel A. Dubin

Abstract: Breast cancer is associated with phosphate toxicity, the toxic effect from dysregulated phosphate metabolism that can stimulate tumorigenesis. Phosphate toxicity and dysregulated phosphate metabolism are also associated with bone mineral abnormalities, including excessive bone mineral loss and deposition. Based on shared associations with dysregulated phosphate metabolism and phosphate toxicity, a hypothesis proposed in the present mixed methods–grounded theory study posits that middle-aged women with incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…Although the study's small cohort likely reduced statistical significance, these results are supported by evidence in the present review, and further clinical investigations are warranted to test the hypothesis that limiting cancer patients to 800-1000 mg or less of phosphorus a day will reduce and prevent cancer promotion and progression. Furthermore, another 2023 study of the cohort by the present authors found that a greater magnitude of abnormal bone mineral density changes (mineral deposition in osteosclerosis followed by mineral loss in osteoporosis) was associated with women self-reporting breast cancer incidence compared to women remaining cancer-free [37]. This finding implicates phosphate toxicity as a potential contributing factor to bone metastases in metastatic breast cancer, which should also be investigated with a low-phosphate dietary intervention.…”
Section: Diet and Cancersupporting
confidence: 48%
“…Although the study's small cohort likely reduced statistical significance, these results are supported by evidence in the present review, and further clinical investigations are warranted to test the hypothesis that limiting cancer patients to 800-1000 mg or less of phosphorus a day will reduce and prevent cancer promotion and progression. Furthermore, another 2023 study of the cohort by the present authors found that a greater magnitude of abnormal bone mineral density changes (mineral deposition in osteosclerosis followed by mineral loss in osteoporosis) was associated with women self-reporting breast cancer incidence compared to women remaining cancer-free [37]. This finding implicates phosphate toxicity as a potential contributing factor to bone metastases in metastatic breast cancer, which should also be investigated with a low-phosphate dietary intervention.…”
Section: Diet and Cancersupporting
confidence: 48%
“…Furthermore, evidence supports that patients with breast cancer have increased levels of phosphorus in their serum [256]. Its toxicity and dysregulated metabolism may be strongly associated with the genesis of this disease [255], as not only does this study point to a high-Pi environment as a cause of secreted factors capable of increasing both endothelial cell migration and tube formation, leading to angiogenesis, tumor growth, and disease progression [257], but also other studies indicate that even higher dietary phosphorus intakes-which include the Western diet-can lead to tumorigenesis, as they may cause the increased proliferation of cells with malignant transformations [258]. Most of the studies mentioned above emphasize the importance of clinically testing low-phosphate diets' effects on patients with breast cancer as it may bring important results and new directions in their treatment.…”
Section: Phosphorusmentioning
confidence: 95%
“…Phosphorus and its homeostasis are also closely associated with calcium and vitamin D, the low levels of which have been reported in the literature for their frequent presence in patients with breast cancer [8]. This leads us to a greater magnitude of chances for osteoporosis and bone mineral density, whose connection to breast cancer remains ambiguous [255]. The most relevant seems to be the hypothesis that, in breast cancer genesis and progression, significant are not only the levels of different micronutrients and vitamins but also the correlations between them.…”
Section: Phosphorusmentioning
confidence: 99%